Superficial Solitary Fibrous Tumor: A Series of 26 Cases. (June 2018) - Feasel, Patrick; Al-Ibraheemi, Alyaa; Fritchie, Karen; Zreik, Riyam T.; Wang, Wei-Lien; Demicco, Elizabeth; Saeb-Lima, Marcela; Goldblum, John R.; Rubin, Brian P.; McKenney, Jesse K.; Ko, Jennifer S.; Billings, Steven D.
Abstract : While superficial (cutaneous/subcutaneous) solitary fibrous tumor (SFT) have been described, definitive diagnosis is difficult due to overlapping features with other tumors. We describe the largest series to date of superficial SFT. For inclusion, SFT had to arise in dermis or subcutis. Twenty-six cases were identified. Patients ranged from 16 to 80 years (mean, 47 y) with a marked female predominance (19 F; 7 M). Tumors involved the head (11), thigh (7), back (3), shoulder (2), upper arm (1), ankle (1), and great toe (1). Mean size was 2.9 cm (range, 1.0 to 7.0 cm). The majority (n=19) had typical histologic features (cellular SFT) with irregular fascicles of spindled cells, staghorn-like blood vessels, and variable amounts of collagen. Necrosis was evident in 3 cases (all <25%). Mitotic activity ranged from 0 to 10 mitotic figures/10 high-power fields (mean, 2 mitotic figures/10 high-power fields). Seventeen of the 18 were positive for STAT6, whereas 21/22 expressed CD34. All were low risk (23/23) by proposed criteria (Demicco and colleagues), including 2 cases with malignant histology. Three could not be risk stratified due to lack of information on tumor size. Follow-up, available on 7 cases, showed no recurrence/metastasis (mean follow-up, 100 mo; range, 2 to 241 mo). Cutaneous SFT are more common in women and most often involve the head. They are usually low risk by proposed criteria and appear to behave in an indolent manner, though larger studies are needed to confirm this. Recognition that SFT may present as a superficial mass will avoid misclassification as other CD34-positive neoplasms that frequently arise in the skin and subcutaneous tissue.